Sosialisasi Peningkatan Gerakan 1 Rumah 1 Jumatik Untuk Pengendalian Demam Berdarah Dengue - Mufidah, Hartalina; Agustin, Ayu Tri; Wijaya, Anas Fadli; Muflihah, Ahdiah Imroatul (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Dengue Hemorrhagic Fever remains a significant health problem in Jember Regency. Jember Regency is among the top three districts with the highest dengue cases in East Java, reporting 781 cases, alongside Malang Regency was 1,224 cases and Ngawi Regency was 673 cases. It situation may be attributed to the lack of public awareness about maintaining a mosquito-free environment and the suboptimal implementation of the "1 House 1 Mosquito Monitor" (G1R1J). Kamal Village is one of the areas with environmental conditions conducive to mosquito breeding and the spread of Dengue Hemorrhagic Fever. Socializing the "1 House 1 Mosquito Monitor" is crucial to increasing public knowledge about the causes of Dengue Hemorrhagic Fever and the importance of Jumantik's role. Objective: The purpose of this service was promote the "1 House 1 Mosquito Monitor" and conduct screening IgM/IgG in Duplang Hamlet, Kamal Village, Arjasa District, Jember Regency Method: This public service was conducted by by socializing the definition of dengue disease, symptoms, prevention and the 1 House 1 Mosquito Monitor using leaflet. Then it was followed by IgG and IgM assay using Rapid test. The number of residents who participated was 16 people. Result: Socialization of One House One Mosquito Monitor were 3M Plus Dengue Prevention (Drain, Cover, Bury), control the mosquito breeding, and Larvacide applications. The IgG and IgM test results showed negative Conclusion: This community service was the successful socialization of the "1 House 1 Mosquito Monitor". None of them had been exposed to the dengue virus.